Risk-Based Internal Audit for the Oversight of Village Funds in Remote Areas: A Literature Review on Risk Mapping, Early Warning, and Fraud Prevention - Edizon Mirino; Dian Ferriswara; Fedianty Augustinah; Sri Kamariyah (International Journal of Humanities and Social Sciences Reviews, 2026)
The governance of village funds represents a critical dimension of decentralized public financial management, particularly in remote and capacity-constrained regions where oversight mechanisms face structural limitations. This literature review examines the role of Risk-Based Internal Audit (RBIA) as a strategic instrument for strengthening the supervision of village fund management through risk mapping, early warning mechanisms, and fraud prevention. Adopting a state-of-the-art literature review design, the study synthesizes peer-reviewed journal articles, conference proceedings, and authoritative institutional reports published primarily within the last five years. The review integrates the analytical lenses of RBIA as articulated in the International Professional Practices Framework, Enterprise Risk Management (ERM) based on ISO 31000 and COSO ERM, the COSO Internal Control–Integrated Framework, and the Fraud Triangle and Fraud Diamond theories. Thematic synthesis reveals that effective village fund oversight depends on the systematic identification and prioritization of risk, the alignment of audit planning with high-risk areas, and the integration of internal control and risk management processes into audit assurance. Furthermore, the literature highlights the growing relevance of early warning systems and audit analytics in enabling proactive detection of emerging risks and potential fraud, although their implementation in remote areas remains constrained by limited data quality, digital infrastructure, and administrative capacity. This review contributes theoretically by consolidating fragmented strands of audit, risk management, and fraud literature into an integrated conceptual framework tailored to village fund governance. Practically, it offers evidence-based insights for auditors, policymakers, and local governments seeking to enhance accountability and risk-responsive oversight in decentralized and remote public finance settings.